Effects of Vitex agnus - castus Extract on After- Discharge Threshold, Seizure Stages and Kindling Acquisition in Male Rats - M Saberi; AR Rezvanizadeh (Institue of Medicinal Plants, ACECR, 2010)
Background: Vitex agnus - castus extract (Vitex) is available in dosage forms for female disorders treatment. This extract has shown controversial effects against seizures induced by Maximal electroshock (MES) or pentylenetetrazole (PTZ).   Objective: In the present study the anti-seizure activity of Vitex against acquisition of amygdala kindling was evaluated in male rats.   Methods: Intact male rats were stereotaxically implanted with a tripolar and 2 monopolar electrodes in amygdala and dura respectively. The threshold of AD emerging was determined in each animal. Then, Vitex or solvent was injected and AD threshold was determined again. Also, Vitex injection was continued daily and seizure stages (S1 to S5) and ADDs were recorded 30 min post Vitex injection till development of full kindling.   Results: Vitex treatment increased the AD threshold significantly more than 2.5 times and decreased the after-discharge duration (ADD). Although, the number of trials increased significantly by Vitex for exhibition of stages 1 (S1) to S3, but this effect was not significant for development of S4 and S5 (generalized seizures). The cumulative ADDs difference between control and Vitex group was only significant for S3 - S5. Conclusions: Vitex may induce a protective effect via increment of stimulation threshold and decrement of ADD at least against focal epilepsy in amygdala neurons. Regarding to its limited effects on kindling acquisition at late stage with generalized seizures, Vitex may postpone the progress of epileptic activity at initial stages.